Perceptions of the teutonic online market and opportunities for adventure travel industry - Loureiro, S. M. C.; Ferreira, E. M.; Witt-Dörring, C. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2017)
This article analyses the potential of e-commerce in the niche market of adventure travels. Tourists have been increasingly booking travels worldwide with the help of online platforms instead of the offline and traditional travel agencies. This situation performs an opportunity to maximize the online travel market. Another important trend is related to e-commerce business that has also been increasing as well as the market for adventure tourism. Under this context, the present article analyzed several existent online platforms for booking adventure travels through a survey of 310 questionnaires in order to find out the Teutonic consumer perception about such platforms.